PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS OVERCLAIM MANFAAT KESEHATAN PADA PRODUK NON-OBAT TANPA DUKUNGAN UJI KLINIK - I Kadek Agus Aditya Firmantara; I Dewa Ayu Komang Candra Astiti (Jurnal Hukum Statuta, 2026)
This study aims to examine the legal construction of consumer protection against health benefit overclaims in non-medicinal supplements lacking clinical trials, as well as the scope of business actors’ liability within the Indonesian legal system. The research employs a normative juridical method, applying both a statutory approach and a conceptual approach. The statutory approach analyzes the hierarchical structure of norms, encompassing Law Number 8 of 1999 on Consumer Protection, the Indonesian Civil Code, and sectoral regulations governing drug and food supervision administered by the Badan Pengawas Obat dan Makanan Republik Indonesia. The conceptual approach is utilized to critically assess the doctrines of overclaim, misrepresentation, duty of care, and the principle of actori incumbit probatio in the allocation of the burden of proof. Primary, secondary, and tertiary legal materials are examined through qualitative analysis using systematic and grammatical interpretation. The study seeks to formulate a coherent legal argument concerning the permissible scope of health claims, the evidentiary standards required for therapeutic representations, and the layered framework of administrative, civil, and criminal liability in consumer protection law, emphasizing legal certainty and substantive justice.